Studies on characterization of nano CaCO3 prepared by the in situ deposition technique and its application in PP-nano CaCO3 composites - Mishra, Satyendra; Sonawane, S. H.; Singh, R. P. (Journal of Polymer Science Part B: Polymer Physics, 2005)
The elegant approach of in situ deposition technique was used for the synthesis of nano CaCO3 the nanosize of particles was confirmed by the X-ray diffraction (XRD) technique. Differential scanning calorimetry (DSC) was used for determination of the enthalpy. The nano CaCO3 polypropylene (PP) composites were prepared by taking 2 and 10 wt % of different nanosizes (21-39 nm) of CaCO3. Conversion of the alpha phase to beta was observed in the case of 2 wt % of a 30-nm sized amount of CaCO3 in a PP composite. The decrement in DeltaH and percent. crystallinity, as well as the increment in melt temperature were recorded for 6 wt % nano CaCO3 with a decrease in nanosize from 39 to 21 nm. The increment in tensile strength with an increase in the amount of nano CaCO3 was observed, and the tower particle size shoved Greater improvement. The improvement in thermal and mechanical properties is because of the formation of a greater number of small spherulites uniformly present in the PP matrix. (C) 2004 Wiley Periodicals, Inc.
Keywords: Crystallization; DSC; mechanical and thermal properties; nano CaCO3; polypropylene; XRD

X-ray crystallographic studies on C-phycocyanins from cyanobacteria from different habitats: marine and freshwater - Satyanarayana, L.; Suresh, C. G.; Patel, A.; Mishra, Satyendra; Ghosh, P. K. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2005)

Ultrasound assisted synthesis of polyacrylic acid-nanoclay nanocomposite and its application in sonosorption studies of malachite green dye - Sonawane, S. H.; Chaudhari, P. L.; Ghodke, S. A.; Parande, M. G.; Bhandari, Vinay M.; Mishra, Satyendra; Kulkarni, R. D. (Ultrasonics Sonochemistry, 2009)
Synthesis of nanoclay nanocomposite has been undertaken by using polyacryalic acid (PAA) in aqueous medium and ultrasound environment and its application in dye removal has been investigated. The synthesized product was characterized by using FTIR and XRD techniques. The sonosorption capacity of the product namely PAA-nanoclay composite was determined by choosing malachite green (MG) dye as a model pollutant. The effects of various parameters such as nanocomposite loading, pH, various process conditions etc. have been studied. On comparing the results obtained with that of nanoclay as an adsorbent, it was found for an initial concentration of 500 mg/l, the PAA-nanoclay nanocomposite exhibited higher percentage of pollutant removal (68%) and for nanoclay it was 54%. The adsorption data has been correlated using Langmuir and Freundlich models. The fit of the Freundlich isotherm model was found to be good in the entire range of concentration for the experimental sorption data obtained on the nanoclay nanocomposite. A plausible reaction mechanism for use of PAA-nanoclay nanocomposite as ail adsorbent is also proposed. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Malachite Green; Nanocomposite; Polyacrylic acid; Sonosorption; Ultrasound

Enhancement of thermal stability and phase relaxation behavior of chitosan dissolved in aqueous l-lactic acid: using `silver nanoparticles' as nano filler - Rana, V. K.; Pandey, Asutosh K.; Singh, Raj Pal; Kumar, B.; Mishra, Satyendra; Ha, Chang-Sik (Macromolecular Research, 2010)
Chitosan films with various compositions of silver nanoparticles were prepared by solution casting with an aqueous solution of chitosan and l-lactic acid. The chitosan/Ag nanocomposites were characterized by wide angle Xray diffraction (WAXD) and UV-vis spectroscopy. An analysis of the surface topography and size of the Ag nanoparticles (<= 100 nm) were characterized by scanning electron microscopy (SEM) and atomic force microscopy (AFM), respectively. Thermogravimetric analysis (TGA/DTA) confirmed the increase in thermal stability with increasing Ag nanoparticle content in the nanocomposites. Dynamic thermal analysis (DMA) was used to examine the phase relaxation behavior of chitosan and its nanocomposites. The conductivity of chitosan/Ag nanocomposites was considered with respect to the frequency. Contact angle measurements were used to characterize the surface twistability, surface cleanliness, and hydrophilic/hydrophobic nature of the surface.
Keywords: Chitosan; conductivity; contact angle; relaxation; silver nanoparticles

Tensile properties, cell adhesion, and drug release behavior of chitosan-silver-gelatin nanohybrid films and scaffolds - Rana, V. K.; Kushwaha, Omkar S.; Singh, RajPal; Mishra, Satyendra; Ha, Chang-Sik (Macromolecular Research, 2010)
Drug-loaded nanohybrid films and porous scaffolds were prepared using chitosan, Ag nanoparticles and gelatin using a solution casting and freeze-drying method, respectively. Gelatin was used to incorporate the cell onto the surface of the scaffolds and the nanohybrid films. 1-[2-hydroxyethyl]-2-methyl-5-nitroimidazole) (Metronidazole (MTZ) was used as a model drug. The small percentage of Ag nanoparticles in the nanohybrid films and scaffolds produced significantly higher cell proliferation and levels of drug release. The tensile properties showed improvement in strength by Ag nanoparticles reinforcement at the expense of elongation.
Keywords: carcinogenic metronidazole; cell proliferation; chitosan-Ag-gelatin nanohybrids; drug release; nano-hybrids; scaffolds

Hierarchical mesoporous bio-polymer/silica composites co-templated by trimethyl chitosan and a surfactant for controlled drug delivery - Rana, Vijay Kumar; Park, Sung Soo; Parambadath, Surendran; Kim, Mi Ju; Kim, Sun-Hee; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Medchemcomm, 2011)
In this communication, we report the facile synthesis of hierarchical mesoporous bio-polymer/silica composite materials with bimodal mesopores using a dual-template of the cationic N,N,N-trimethyl chitosan (TMCs) and the anionic sodium dodecyl sulfate (SDS) via one-step synthetic strategy. Tetraethoxysilane (TEOS) was used as a silica source. The nitrogen adsorption/desorption measurements and transmission electron microscopy analysis showed the hierarchical structure of the mesoporous bio-polymer/silica composites with bimodal mesopores having an average pore size of 5-7 nm with the visible voids between the silica nanoparticles, which allow the mesoporous bio-polymer/silica composites to encapsulate a large number of guest drug molecules, Ibuprofen (IBU) or 5-fluorouracil (5-FU), due to their high surface area and pore volume. In addition, the mesoporous chitosan-silica composites also had a long term biocompatibility for the target release of the drug molecules to the CEM cells, MCF cells, etc. as well as a pH sensitive controlled release behavior of the drug molecules.

Novel synthesis of nano-calcium carbonate (CaCO3)/polystyrene (PS) core-shell nanoparticles by atomized microemulsion technique and its effect on properties of polypropylene (PP) composites - Mishra, Satyendra; Chatterjee, Aniruddha; Singh, RajPal (Polymers for Advanced Technologies, 2011)
Calcium carbonate (CaCO3)/polystyrene (PS) nanoparticles (< 100 nm) with core-shell structure were synthesized by atomized microemulsion technique. The polymer chains were anchored onto the surface of nano-CaCO3 through triethoxyvinyl silane (TEVS) as a coupling agent. Ammonium persulfate (APS), sodium dodecyl sulfate (SDS) and n-pentanol were used as initiator, surfactant, and cosurfactant, respectively. Polymerization mechanism of core-shell latex particles was discussed. Encapsulation of nano-CaCO3 by PS was confirmed by using transmission electron microscope (TEM). Grafting percentage of core-shell particles was investigated by Thermogravimetric Analyzer (TGA). Nano-CaCO3/PS core-shell particles were characterized by Fourier transform infrared (FTIR) spectrophotometer and differential scanning calorimeter (DSC). The results of FTIR revealed existence of a strong interaction at the interface of nano-CaCO3 particle and PS, which implies that the polymer chains were successfully grafted onto the surface of nano-CaCO3 particle through the link of the coupling agent. In addition, TGA and DSC results indicated an enhancement of thermal stability of core-shell materials compared with the pure nano-PS. Nano-CaCO3/PS particles were blended with polypropylene (PP) matrix on Brabender Plastograph by melt process with different wt% of loading (i.e. 0.1-1 wt%). The interfacial adhesion between nano-CaCO3 particles and PP matrix was significantly improved when the nano-CaCO3 particles were grafted with PS, which led to increased thermal, rheological, and mechanical properties of (nano-CaCO3/PS)/PP composites. Scanning electron microscope (SEM) and atomic force microscope (AFM) images showed a perfect dispersion of the nano-CaCO3 particles in PP matrix. Copyright (C) 2011 John Wiley & Sons, Ltd.
Keywords: atomized microemulsion; core-shell nanoparticles; mechanical properties; polypropylene (PP); Rheological properties; Thermal properties

Synthesis and drug-delivery behavior of chitosan-functionalized graphene oxide hybrid nanosheets - Rana, Vijay Kumar; Choi, Myeon-Cheon; Kong, Jin-Yeon; Kim, Gwang Yeon; Kim, Mi Ju; Kim, Sun-Hee; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Macromolecular Materials and Engineering, 2011)
Chitosan-functionalized graphene oxides (FGOCs) were successfully synthesized. FGOCs were found to significantly improve the solubility of the GO in aqueous acidic media. The presence of organic groups was confirmed by means of XPS and TGA. Restoration of the sp(2) carbon network and exfoliation of graphene sheets were confirmed by Raman spectroscopy, UV-visible spectroscopy and WAXD. The SEM and AFM investigations of the resultant FGOCs showed that most of the graphene sheets were individual and few were layered. Controlled release behavior of Ibuprofen and 5-fluorouracil was then investigated. We found that FGOCs are a promising new material for biological and medical applications.
Keywords: Biocompatibility; Chitosan; drug delivery systems; functionalization of polymers; solution properties

Heterocyclic tri-urea isocyanurate bridged groups modified periodic mesoporous organosilica synthesized for Fe(III) adsorption - Rana, Vijay Kumar; Selvaraj, M.; Parambadath, Surendran; Chu, Sang-Wook; Park, Sung Soo; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Journal of Solid State Chemistry, 2012)
To achieve a high level of heavy metal adsorption, 1,1',1 `'-(1,3,5-triazine-2,4,6-triyl)tris(3-(3-(triethoxysilyl) propyl)urea) (TTPU) was synthesized as a novel melamine precursor and incorporated on the silica surface of periodic mesoporous organosilica (PMO). The melamine modified PMOs (MPMOs) were synthesized under acidic conditions using TTPU, tetraethylorthosilicate (TEOS) and Pluronic P123 as a template and the modified PMOs were characterized using the relevant instrumental techniques. The characteristic materials were used as adsorbents for the adsorption of Fe(III) ions. Fe(III) adsorption studies revealed MPMO-7.5 to be a good absorbent with higher adsorption efficiency than other MPMOs. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Adsorption efficiency; Fe(III) adsorption; Melamine; Periodic mesoporous organosilica (PMO)

Chitosan and chitosan-co-poly(epsilon-caprolactone) grafted multiwalled carbon nanotube transducers for vapor sensing - Rana, Vijay Kumar; Akhtar, Shamim; Chatterjee, Sudipta; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Journal of Nanoscience and Nanotechnology, 2014)
Vapor sensitive transducer films consisting of chitosan grafted (CNT-CS) and chitosan-co-polycaprolactone grafted (CNT-CS-PCL) multiwalled carbon nanotubes were prepared using a spray layer-by-layer technique. The synthesized materials (CNT-CS and CNT-CS-PCL) were characterized by Fourier transform infrared spectroscopy, C-13 CP/MAS solid state nuclear magnetic resonance spectroscopy and thermogravimetric analysis. Both CNT-CS and CNT-CS-PCL transducers were analyzed for the response of volatile organic compounds and toluene vapors. The ranking of the relative resistance (A(r)) for both chitosan based transducers were as follows: toluene < chloroform < ethanol < methanol. The CNT transducer (CNT-CS) was correlated selectively with an exponential law to the inverse of Flory-Huggins interaction parameters, chi(12). Dosing the films on the interdigitated electrodes with methanol, ethanol, chloroform and toluene vapors increased the film resistance of CNT-CS but decreased the resistance of CNT-CS-PCL compared to that of the reported transducers.
Keywords: Biocompatibility; Chitosan; MWCNTs; Poly(epsilon-caprolactone); Vapour Sensing

Controlling necking in extrusion film casting using polymer nanocomposites - Rokade, Dhammaraj; Azad, Lal B.; Poddar, Suparna; Mishra, Satyendra; Pol, Harshawardhan V.; Shukla, Rishab (Journal of Macromolecular Science Part B-Physics, 2017)
The research described was concerned with the effect of layered-silicate-based organically modified nanoclay fillers on controlling the extent of necking in a polymer melt extrusion film casting (EFC) process. We show that a linear polythylene resin (such as a linear low-density polyethylene-LLDPE) filled with a very low percentage of well-dispersed (or intercalated) nanoclay displays an enhanced resistance to the necking phenomenon. In general, melt-compounded nanoclay-filled LLDPE resin formulations displayed a higher final film width (less necking), thus a lower final film thickness (greater draw down for the same draw ratio), and cooled down faster when compared to the base LLDPE resin. Incorporation of nanoclay filler in the mainly linear chain LLDPE resin led to significant modification of the melt rheological properties that, in turn, affected the melt processability of these formulations. Primarily, the intercalated nanoclay-filled LLDPE formulations displayed the presence of strain-hardening in unaxial extensional rheology. Additionally, the presence of well-dispersed nanoclay in the LLDPE resin led to a display of prominent extrudate swell indicating the presence of melt elasticity in such formulations. The presence of melt elasticity, as shown by shear rheology and strain-hardening, observed by uniaxial extensional rheology, contributed to the LLDPE nanoclay formulations displaying an enhanced resistance to necking for these films. It can be concluded that linear chain polymers susceptible to necking in an EFC process can be made more resistant to such necking by using nanoclay fillers at very low levels of loading.

Polylactic acid (PLA) biocomposites filled with waste leather buff (WLB) - Ambone, Tushar; Joseph, Seena; Deenadayalan, E.; Mishra, Satyendra; Jaisankar, S.; Saravanan, P. (Journal of Polymers and the Environment, 2017)
A large amount of leather waste is generated from tanning industries and most of which are disposed of landfill or discharged into the natural water bodies without any treatment, causing environmental problems. The aim of this study is to develop eco-biocomposites using waste leather buff (WLB) as filler in Polylactic acid (PLA) matrix to reduce the environmental issues and provide sustainable solution. WLB/PLA composites were prepared by twins-screw micro extruder varying the WLB content from 2% to 30 wt%. These composite were extensively characterise by several techniques. Tensile properties of the composites showed addition of WLB resulted in improvement of tensile property of composite and reduction in percentage crystallinity of PLA matrix observed with increase in WLB content. The effect of WLB on properties of interfacial adhesion and dispersion in WLB/PLA composites were studied by SEM. Wettability of composites was tested by contact angle and water absorption studies. WLB/PLA composite showed increase in water absorption with WLB loading. These WLB/PLA composite could be used to develop low cost eco-friendly product material.